Pengaruh Model Direct Instruction Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Pada Materi Teorema Pythagoras Kelas VIII SMP - Rizka Maulidatun Nadifah; Istanade Habibi Nasrullah; Rizal Kurniawan; Nur Wiji Sholikin (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze the effect of the Direct Instruction model on improving students’ mathematical conceptual understanding in the Pythagorean Theorem topic for eighth-grade students. This research employed a quantitative approach using a pre-experimental method with a One-Group Pretest-Posttest Design. The participants consisted of 30 eighth-grade students at MTs Bustanul Ulum selected through purposive sampling. Data were collected using an essay-based mathematical conceptual understanding test administered before and after the treatment. Data analysis was conducted using descriptive statistical analysis, normality testing, Paired Sample t-Test, Wilcoxon Signed-Rank Test, and Normalized Gain (N-Gain) analysis. The results showed that the students’ mean score increased from 67.50 in the pretest to 85.17 in the posttest, with an improvement of 17.67 points. The Paired Sample t-Test showed a significance value of 0.000 < 0.05 with a t-value of 13.293, while the Wilcoxon Signed-Rank Test also indicated a significance value of 0.000. The N-Gain analysis resulted in a score of 0.5422 or 54.22%, which was categorized as moderate and sufficiently effective. These findings indicate that the Direct Instruction model effectively improves students’ mathematical conceptual understanding through structured learning activities, explicit explanations, guided practice, and continuous feedback. Therefore, the Direct Instruction model can be considered an effective alternative strategy for mathematics teachers to enhance students’ understanding of the Pythagorean Theorem concept.